Design, Construction, and Installation of a Drainage Lysimeter for Use on Sandy, Well-Drained Soils under Turfgrass - Jovana Radovanovic; Eban Z. Bean; Alexander J. Reisinger (EDIS)
Using lysimeters to collect water quality samples can provide a better understanding of nutrient or other solute migration below the surface, which can inform landscape management for environmental protection. This 6-page publication presents the materials, construction, installation, and management of a specific drainage lysimeter design in a step-by-step format. Written by Jovana Radovanovic, Eban Z. Bean, and Alexander J. Reisinger, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2021.